2016
DOI: 10.3390/jcdd3010009
|View full text |Cite
|
Sign up to set email alerts
|

TLR-4 and CD14 Genotypes and Soluble CD14: Could They Predispose to Coronary Atherosclerosis?

Abstract: Background: Inflammatory mechanisms are key to the pathogenesis of atherosclerosis. Functional polymorphisms of TLR-4, Asp299Gly and Thr399Ile, CD14 promoter area C260T polymorphism and plasma levels of soluble CD14 are studied in subjects with Coronary Artery Disease (CAD). Methods: DNA was obtained from 100 human paraffin-embedded aortic specimens, from cadavers with known coronary atheromatosis (Group A) and 100 blood samples from patients with CAD, as detected by cardiac Multi-Detector-row-Computed-Tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…More specifically, genomic DNA from peripheral blood was isolated using a NucleoSpin Blood kit (Macherey–Nagel, GmbH & Co. KG, Düren, Germany) according to the manufacturer’s instructions. Genotyping in all selected polymorphisms was performed by PCR-RFLP analysis for the TLR-4 Asp299Gly (rs4986790) and TLR-4 Thr399Ile (rs4986791) polymorphisms, as previously described [ 63 ]. Specific, primers for TLR-4 Asp299Gly were: forward (5′-GATTAGCATACTTAGACTACTACCTCCATG-3′) and reverse (5′-GATCAACTTCTGAAAAAGCATTCCCAC-3′) and for TLR-4 Thr399Ile were forward (5′-GGTTGCTGTTCTCAAAGTGATTTTGGGAGAA-3′) and reverse (5′-CCTGAAGA CTGGAGAGTGAGTTAAATGCT-3′).…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, genomic DNA from peripheral blood was isolated using a NucleoSpin Blood kit (Macherey–Nagel, GmbH & Co. KG, Düren, Germany) according to the manufacturer’s instructions. Genotyping in all selected polymorphisms was performed by PCR-RFLP analysis for the TLR-4 Asp299Gly (rs4986790) and TLR-4 Thr399Ile (rs4986791) polymorphisms, as previously described [ 63 ]. Specific, primers for TLR-4 Asp299Gly were: forward (5′-GATTAGCATACTTAGACTACTACCTCCATG-3′) and reverse (5′-GATCAACTTCTGAAAAAGCATTCCCAC-3′) and for TLR-4 Thr399Ile were forward (5′-GGTTGCTGTTCTCAAAGTGATTTTGGGAGAA-3′) and reverse (5′-CCTGAAGA CTGGAGAGTGAGTTAAATGCT-3′).…”
Section: Methodsmentioning
confidence: 99%
“…Some clinical studies have demonstrated that the effects of polymorphisms of genetic variants of the human TLR4 gene, located on chromosome 9, on the progression of the atherosclerosis, is controversial (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%